Blood‐induced cartilage damage alters the ankle joint load during walking. Issue 11 (22nd May 2020) - Eerdekens, Maarten; Peerlinck, Kathelijne; Staes, Filip; Pialat, Jean‐Baptiste; Hermans, Cedric; Lobet, Sébastien; Scheys, Lennart; Deschamps, Kevin
Abstract: Ankle cartilage damage due to repeated joint bleeds often leads to altered gait in adult patients with hemophilia. It is therefore of clinical importance to develop an understanding of the biomechanical gait features in hemophilia patients with and without blood‐induced cartilage damage and age‐matched control subjects. We recruited a control group (n = 17), patients with hemophilia (PwH) without blood‐induced ankle cartilage damage (PwH_NoCartDam, n = 5) and PwH with severe blood‐induced ankle cartilage damage (PwH_CartDam, n = 19). We collected three‐dimensional gait analysis data with following outcome variables in the ankle, Chopart and the first metatarsophalangeal (MTP 1) joints: range of motion (ROM) during stance phase, peak joint moment and powers. Biomechanical loading (BW) was quantified as the joint reaction forces using inverse dynamic analysis. Loading rate (BW/s) and impulse (BW*s) were calculated between 50% and 70% of stance phase. All biomechanical variables of the ankle joint were significantly lowered in the PwH_CartDam group compared with both the control subjects and the PwH_NoCartDam group. No compensatory biomechanical function was observed in other foot joints. An ankle loading rate of 2.64 ± 0.83 BW/s was observed in the control group, which was significantly higher than 1.75 ± 0.43 BW/s ( P = .049) and 1.22 ± 0.59 BW/s ( P < .001) in respectively the PwH_NoCartDam group and PwH_CartDam group. Patients with severe blood‐induced cartilage damage demonstrated a (mal)adaptive gait strategy as they experience difficulties to properly unload the ankle cartilage during walking.